Human Testicular Germ Cells, a Reservoir for Zika Virus, Lack Antiviral Response Upon Zika or Poly(I:C) Exposure - Kuassivi, Ohiniba Nadège; Abiven, Hervé; Satie, Anne-Pascale; Cartron, Matéo; Mahé, Dominique; Aubry, Florence; Mathieu, Romain; Rebours, Valérie; Le Tortorec, Anna; Dejucq-Rainsford, Nathalie (Frontiers in Immunology, 2022)
Zika virus (ZIKV) is an emerging teratogenic arbovirus that persists in semen and is sexually transmitted. We previously demonstrated that ZIKV infects the human testis and persists in testicular germ cells (TGCs) for several months after patients’ recovery. To decipher the mechanisms underlying prolonged ZIKV replication in TGCs, we compared the innate immune response of human testis explants and isolated TGCs to ZIKV and to Poly(I:C), a viral RNA analog. Our results demonstrate the weak innate responses of human testis to both ZIKV and Poly(I:C) as compared with other tissues or species. TGCs failed to up-regulate antiviral effectors and type I IFN upon ZIKV or Poly(I:C) stimulation, which might be due to a tight control of PRR signaling, as evidenced by the absence of activation of the downstream effector IRF3 and elevated expression of repressors. Importantly, exogenous IFNβ boosted the innate immunity of TGCs and inhibited ZIKV replication in the testis ex vivo, raising hopes for the prevention of ZIKV infection and persistence in this organ.